COMPARISON OF THE HYDROLOGICAL CHARACTERISTICS OF 3 SMALL EXPERIMENTAL HOLM OAK FORESTED CATCHMENTS IN NE SPAIN IN RELATION TO LARGER AREAS - Piñol, J; Avila, a; Escarre, A; LLEDO, M J; Rodà, F (VEGETATIO, 1992)
Precipitation and streamflow have been measured in three small (0.04-0.52 km2) experimental catchments covered by dense holm oak (Quercus ilex L.) forests. Two of them are in the Prades mountains and one in the Montseny mountains (NE Spain). Here we test the hydrological representativeness of these catchments against the streamflow record at two nearby larger (34-60 km2) catchments, one from each massif. Comparisons of (i) annual streamflow, (ii) seasonal distribution of streamflow, and (iii) flow duration curves were made. At Prades, for the period of common record, mean annual precipitation was about 580 mm, and mean annual streamflow 44-81 mm at the two experimental catchments and 102 mm at the larger one. Most streamflow occurred during winter and spring in the three catchments. At Montseny, rainfall was higher, and mean annual streamflow was 495 mm in the experimental catchment, and 760 mm in the larger catchment, though these data were obtained in different periods in each catchment. Streamflow was roughly equal in autumn, winter and spring. At both sites flow duration curves were fairly similar in the small experimental catchments and the larger catchments. The higher streamflow at Montseny is reflected in its flow duration curves being well above those at Prades. The experimental catchments at Prades are thus fairly representative of the investigated hydrological characteristics. At Montseny, hydrological differences between the experimental catchment and the larger catchment are probably due to the higher mean altitude of the latter and to the non-overlapping periods of their streamflow records.
Keywords: EXPERIMENTAL CATCHMENT; montseny; prades; QUERCUS-ILEX; STREAMFLOW; Water budget

Streamwater pH, alkalinity, p CO 2 and discharge relationships in some forested Mediterranean catchments - Piñol, J; Avila, a (Journal of Hydrology, 1992)
The streamwater chemistry of four catchments at Prades and one catchment at Montseny (NE Spain) is described and the relationships between streamwater alkalinity, pH and pCO 2 with discharge and that between pH and alkalinity are highlighted. At Montseny, results from a subsurface seepage are also presented. The Prades and Montseny catchments have similar vegetation (dense forest of holm oak. Quercus ilex L.) and lithology (phyllites). However, the catchments differ strongly in their hydrological behaviour: only 8-15% of the rainfall passes to the stream from the two gauged Prades catchments, whereas the Montseny catchment provides 50% of rainfall to the stream. Hence the mineralization of streamwaters is much higher in the Prades catchments. All the streams studied show an inverse relationship between alkalinity and discharge. Although pH also decreases with discharge in the Montseny catchment. it remains high during high flows in the Prades catchments. The Prades streamwater chemistries are determined by the solubility equilibrium of calcite: at high flows alkalinity decreases and, as a result of calcite solubility controls, this change results in an increase in pH. Consequently, pH and log(alkalinity) are either negatively correlated or uncorrelated in the Prades streams. At Montseny, the relationship between pH and alkalinity is significantly positive: calcite solubility controls do not come into play. All waters analyzed show an excess pCO 2 (epC02) with respect to atmospheric concentrations. The highest epC02 values usually correspond to low flows. However, study of the variation of epCO2 during 15 individual storm events sampled at Montseny shows that epCO 2 increases with discharge. At Prades, the degassing of epCO 2 in the stream channel produces calcite precipitation.
Keywords: Catchments; montseny; prades; precipitation (voyant); Streamwater chemistry